36 Involving patients and families in tracheostomy care and quality improvement initiatives: a global perspective. (31st October 2017) - Manji, Arif; Bergman, Lina; Swords, Chloe; Ward, Erin; McCormick, Michael; Arora, Asit
Abstract : Aim: Previous work describing patient and family outcomes after tracheostomy indicated that patients do not feel prepared at the time of discharge. The aim of our work was threefold: i. To assess the current provision of tracheostomy care within hospitals in the global community. ii. To improve hospital provision of tracheostomy quality improvement projects. iii. To champion clinician-patient interactions to improve the future of tracheostomy care. Methods: An electronic survey was developed to review the perspective of healthcare professionals with respect to tracheostomy care. Confidence levels were assessed using a 5-point Likert scale. Surveys were disseminated via email. Following completion, participants participated in a free online webinar and completed a post-webinar survey. Participant confidence was compared pre-and post-webinar using Mann-Whitney. Results: Only 23% of institutions provided elective patients with the opportunity to meet a tracheostomy patient prior to surgery. 52% of participants' institutions participated in tracheostomy quality improvement initiatives and fewer than one quarter involved patients in quality improvement projects. Following the webinar, participant confidence regarding discussing emergency and home nursing tracheostomy care improved (p=0.025, p=0.001). Importantly, participants reported increased confidence in their ability to involve patients and their families in quality improvement interventions (p=0.001). Conclusions: Current hospital and discharge provision of tracheostomy care can be improved. Educational interventions, such as webinars, act as an aid to improve confidence and provide professionals with strategies to change their practice. The current practice of clinician-led audit is becoming less viable. Future initiatives should focus upon patient-centred and patient-led outcomes to ensure excellence in deliverance of healthcare.